You are on page 1of 4

Commonly Used Taylor Series

series 1 1−x

when is valid/true

= =

1 + x + x2 + x3 + x4 + . . .

note this is the geometric series. just think of x as r

xn
n=0

x ∈ (−1, 1)

e

x

=

x x x 1 + x + + + + ... 2! 3! 4! xn n! n=0

2

3

4

so: e=1+1+ e
(17x)

1 2!

+

1 3!

+

1 4!

+ ...
∞ 17n xn n! n=0

=

∞ (17x)n n=0 n!

=

=

x∈R

cos x

=

x4 x6 x8 x2 + − + − ... 1 − 2! 4! 6! 8!

note y = cos x is an even function (i.e., cos(−x) = + cos(x)) and the taylor seris of y = cos x has only even powers.

=

(−1)n
n=0

x2n (2n)!

x∈R

sin x

=

x5 x7 x9 x3 + − + − ... x − 3! 5! 7! 9!

note y = sin x is an odd function (i.e., sin(−x) = − sin(x)) and the taylor seris of y = sin x has only odd powers.

=

(−1)(n−1)
n=1

x2n−1 or = (2n − 1)!

(−1)n
n=0

x2n+1 (2n + 1)!

x∈R

ln (1 + x)

= =

x −

x2 x3 x4 x5 + − + − ... 2 3 4 5 xn or = n

question: is y = ln(1 + x) even, odd, or neither?

(−1)(n−1)
n=1

(−1)n+1
n=1

xn n

x ∈ (−1, 1]

tan−1 x

= =

x −

x3 x5 x7 x9 + − + − ... 3 5 7 9 x2n−1 or = 2n − 1

question: is y = arctan(x) even, odd, or neither?

(−1)(n−1)
n=1

(−1)n
n=0

x2n+1 2n + 1

x ∈ [−1, 1]

1

e. . pN (x0 ) = f (N ) (x0 ) . x0 ∈ I . .Math 142 Taylor/Maclaurin Polynomials and Series Prof.e. the constants cn ’s are chosen so that: pN (x0 ) = f (x0 ) pN (x0 ) = f (1) (x0 ) pN (x0 ) = f (2) (x0 ) . i. The N th -order Maclaurin polynomial for y = f (x) is just the N th -order Taylor polynomial for y = f (x) at x0 = 0 and so it is p N ( x) = Definition 2. . . 1 (N ) (2) (1) f (n) (0) n x . The constant cn is the nth Taylor coefficient of y = f (x) about x0 . (closed form) The Maclaurin series for y = f (x) is just the Taylor series for y = f (x) at x0 = 0. It can also be written in closed form. .. Next consider a function. . Girardi Fix an interval I in the real line (e. . 2. } . n ! n=0 ∞ ← the sum keeps on going and going. as pN (x) = f (n) (x0 ) (x − x0 )n . 1Here we are assuming that the derivatives y = f (n) (x) exist for each x in the interval I and for each n ∈ N ≡ {1. 3. 0! 1! 2! N! Formula (open form) is in open form. 3. the sum stops . as P∞ (x) = f (n) (x0 ) (x − x0 )n . 5. .. by using sigma notation. N . 19)) and let x0 be a point in I . by using sigma notation.e. . whose domain is I . The N th -order Taylor polynomial for y = f (x) at x0 is: f (N ) (x0 ) f (x0 ) (x − x0 )2 + · · · + ( x − x0 ) N . Definition 1.g. . 0! 1! 2! n! The Taylor series can also be written in closed form. . i. 2! N! which can also be written as (recall that 0! = 1) pN (x) = f (x0 ) + f (x0 )(x − x0 ) + pN (x) = (open form) f (0) (x0 ) f (1) (x0 ) f (2) (x0 ) f (N ) (x0 ) + (x−x0 )+ (x−x0 )2 +· · ·+ (x−x0 )N ← a finite sum. n ! n=0 f (n) (x0 ) n! N (closed form) So y = pN (x) is a polynomial of degree at most N and it has the form N pN (x) = n=0 cn (x − x0 )n where the constants cn = are specially chosen so that derivatives match up at x0 . . 2 . 4. I might be (−17. 2! n! (open form) P∞ (x) = f (x0 ) + f (x0 )(x − x0 ) + which can also be written as f (0) (x0 ) f (1) (x0 ) f (2) (x0 ) f (n) (x0 ) P∞ (x) = + (x−x0 )+ (x−x0 )2 +· · ·+ (x−x0 )n +. 2. i. n! n=0 N The Taylor series for y = f (x) at x0 is the power series: f (n) (x0 ) f ( x0 ) (x − x0 )2 + · · · + ( x − x0 ) n + . f: I →R and whose derivatives f (n) : I → R exist on the interval I for n = 1. .

does f (x) = P∞ (x) ? Question (2) is going to take some thought.e. the sum stops at N . Notice 5. So 7. Taking the limN →∞ of both sides in equation (3). We would LIKE TO HAVE THAT ∞ f (n) (x0 ) ?? f (x) = (x − x0 )n n ! n=0 In other notation: ← the sum keeps on going and going . ?? f (x) = P∞ (x) Well. for f to equal to its Taylor series. Recall 6. we see that f (x) = if and only if N →∞ f (n) (x0 ) (x − x0 )n n ! n=0 ∞ ← the sum keeps on going and going . let’s think about what needs to be for f (x) = P∞ (x). this is where Mr. If N →∞ lim |RN (x)| = 0 f (n) (x0 ) ( x − x0 ) n . limN →∞ RN (x) = 0 if and only if limN →∞ |RN (x)| = 0 . Taylor comes to the rescue! 2 2According to Mr.. n ! n=0 ∞ (4) then f (x) = So we basically want to show that (4) holds true. The N th -order Remainder term for y = f (x) at x0 is: RN (x) = f (x) − PN (x) where y = PN (x) is the N th -order Taylor polynomial for y = f (x) at x0 . i. his Remainder Theorem (see next page) was motivated by coffeehouse conversations about works of Newton on planetary motion and works of Halley (of Halley’s comet ) on roots of polynomials. ?? f (x) ≈ PN (x) and the question is where y = P∞ (x) is the Taylor series of y = f (x) at x0 . does the series converge to what we would want it to converge to.a. Taylor) series P∞ (x) = f (n) (x0 ) (x − x0 )n n ! n=0 ∞ (1) converge (usually the Root or Ratio test helps us out with this question).k.e. ← a finite sum. i. So f (x) = PN (x) + RN (x) that is f (x) ≈ PN (x) We often think of all this as: f ( x) ≈ f (n) (x0 ) ( x − x0 ) n n ! n=0 N def (2) (3) within an error of RN (x) . Definition 4. If the power/Taylor series in formula (1) does indeed converge at a point x.Big Questions 3. lim RN (x) = 0 .. Taylor. How to do this? Well. 3 . For what values of x does the power (a.

y = f (N +1) (x). Then. M N +1 |x − x0 | (N + 1)! (7) Version 3: for the whole interval I and all N ∈ N. = f (x) − PN (x) theorem = Note that formula (5) implies that |RN (x)| = f (N +1) (c) (N +1) |x − x0 | . There exists c between x and x0 so that RN (x) def 3 f (N +1) (c) (x − x0 )(N +1) . (N + 1)! (6) Version 2: for the whole interval I and a fixed N ∈ N. (5) (N + 1)! So either x ≤ c ≤ x0 or x0 ≤ c ≤ x.e.. The proof uses the Mean Value Theorem. by So 7. max f (N +1) (c) ≤ M . lim N →∞ lim |RN (x)| = 0 f (n) (x0 ) (x − x0 )n n ! n=0 ∞ for each x ∈ I . Remark: This is a Big Theorem by Taylor. Thus. by formula (7) and the Squeeze Theorem. exists for each x ∈ I and each N ∈ N.Taylor’s Remainder Theorem Version 1: for a fixed point x ∈ I and a fixed N ∈ N. 4 Now assume that we can find a sequence {MN }∞ N =1 so that max f (N +1) (c) ≤ MN c∈I for each N ∈ N and also so that MN N +1 |x − x0 | = 0 N →∞ (N + 1)! for each x ∈ I . Then |RN (x)| ≤ for each x ∈ I .3 Assume we can find M so that the maximum of f (N +1) (x) on the interval I i. f (x) = for each x ∈ I . 4Here we assume that y = f (N ) (x). exists for each x ∈ I . Remark: This follows from formula (6). i.e. 3Here we assume that the (N + 1)-derivative of y = f (x). c∈I ≤ M . See the book for the proof. 4 . So we do not know exactly what c is but atleast we know that c is between x and x0 and so c ∈ I .